When the Sacroiliac Joint is the Culprit: A Multicenter Investigation of an Uncommon Primary Location for Pediatric Musculoskeletal Infections - Ian Kuckelman, MD, MPH; Alexander R. Farid, MD; Lucas Hauth, BS; Helena Franco, MD, MSurg, MMSc; Samuel Mosiman, MS; John M. Flynn, MD; Mininder S. Kocher, MD, MPH; Kenneth J. Noonan, MD, MHCDS (Elsevier, 2024)
ABSTRACT: Background: The purpose of this multicenter study is to describe findings that facilitate making an accurate diagnosis of pediatric musculoskeletal infections affecting the sacroiliac joint (SIJ) while identifying factors associated with surgical treatment or protracted clinical course. Methods: A query was conducted between January 1, 2000 and March 2, 2021 at 3 large academic institutions. We included patients <18 years old with clinical findings consistent with pyogenic SIJ infection and either positive specimen cultures (blood or bone) or SIJ involvement on imaging. We used descriptive statistics for analysis and then employed regression models to evaluate which variables could predict primary outcomes: operative intervention, antibiotic duration, and complications. Results: Sixty-nine patients met the inclusion criteria. Common presenting symptoms were pain localized to the posterior pelvis or SIJ (94%) and difficulty with ambulation (94%). The irritable hip motion was present in 93% of patients (flexion, abduction, and external rotation test was positive in 17/51 cases). Associated symptoms were present in 48% of patients (chills or sweats, 21.7%; nausea/vomiting, 15.9%). Radiographs performed on the day of admission (86%) were predominantly normal (89%). Forty-four out of 47 patients underwent magnetic resonance imaging, with pertinent findings including edema and bony changes in the SIJ (54% of patients). Exactly 26.1% of patients had CT-guided aspirate, and 20.3% of patients had at least 1 operative procedure. Recurrent (8.7%) or chronic (5.8%) infection was uncommon, as were inpatient complications (8.7%). Maximum C-reactive protein throughout admission was positively associated with the odds of surgery; increased age was positively associated with the odds of inpatient complications (P < .05). Total duration of antibiotic therapy, including both inpatient and outpatient antibiotics, was significantly longer in patients in the operative group (P = .01). Conclusions: In this multicenter study investigating pediatric SIJ infections, we identify several key factors that can aid in diagnosis and management. Early magnetic resonance imaging and specimen cultures are preferred to confirm the diagnosis. In uncertain cases, CT-guided biopsy or operative intervention can be effective for both diagnosis and treatment. Some patients may require one or multiple procedures and extended antibiotic duration, yet the outcome is largely satisfactory. Key Concepts: (1) Despite the variable presentation of pediatric sacroiliac joint (SIJ) infections, common features such as fever, localized pain, and difficulty ambulating should prompt comprehensive workup including physical examination, laboratory tests, and imaging. (2) Magnetic resonance imaging remains the ideal imaging modality for identifying SIJ involvement, often demonstrating purulence and adjacent muscle edema. (3) Elevated inflammatory markers like C-reactive protein (CRP) and leukocytosis are common, with higher CRP levels potentially signifying a more severe infection and increased likelihood of operative intervention. (4) Antibiotics are the mainstay of treating SIJ infections, with operative management reserved for certain patients, including those with extensive infection or high-risk factors like older age and higher body mass index. Level of Evidence: IV, Retrospective Case Series